Respuesta :
d
I would do the math out. but I'm lazy. message me if you want me to
I would do the math out. but I'm lazy. message me if you want me to
Answer:
option D
Step-by-step explanation:
To find inverse , we replace f(x) by y. then swap the variables x and y. finally solve the equation for y
(a) y=(x+1)/6
x= (y+1)/6
6x= y+1
y=6x-1 that is our g(x)
(b) y=(x-4)/19
x= (y-4)/19
19x=y-4
y=19x+4 that is our g(x)
(c) y=5x
x=5y
y= x/5 that is our g(x)
(d) y=x/(x+20)
[tex]x=\frac{y}{y+20}[/tex]
cross multiply
x(y+20)= y
xy+20x= y
subtract xy on both sides
20x= y-xy
20x= y(1-x)
so y= 20x/(1-x) that is not our g(x)